2011
DOI: 10.1002/ptr.3364
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmitter Metabolic Enzymes and Antioxidant Status on Alzheimer's Disease Induced Mice Treated with Alpinia galanga (L.) Willd

Abstract: Amyloid β₂₅₋₃₅ (Aβ) peptide may be neurotoxic during the progression of Alzheimer's disease by eliciting reactive oxygen species. The use of folklore medicine is prevalent and plants which possess a rejuvenating property are a large source of natural antioxidants that might afford leads for the development of novel drugs in neurodegenerative disorders. The study was designed to investigate the effect of an ethanol extract of Alpinia galanga (L.) Willd (EAG) on oxidative stress induced Alzheimer's type amnesia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Boyd-Kimball et al [66] reported that glutathione upregulation protected neuron against oxidative stress and neurotoxicity induced by A(1-42) in the AD affected brain. Hanish Singh et al [67] reported that ethanolic extract of Alpinia galangal improved the antioxidant status and inhibited the acetylcholine esterase activity in AD mice. Our research group from Oman reported the beneficial effects of natural products including pomegranate and figs on AD transgenic mice models [62, 6877].…”
Section: Natural Products and Alzheimer's Diseasementioning
confidence: 99%
“…Boyd-Kimball et al [66] reported that glutathione upregulation protected neuron against oxidative stress and neurotoxicity induced by A(1-42) in the AD affected brain. Hanish Singh et al [67] reported that ethanolic extract of Alpinia galangal improved the antioxidant status and inhibited the acetylcholine esterase activity in AD mice. Our research group from Oman reported the beneficial effects of natural products including pomegranate and figs on AD transgenic mice models [62, 6877].…”
Section: Natural Products and Alzheimer's Diseasementioning
confidence: 99%
“…Reported active constituents, including total oligomeric flavonoid fractions, nootkatone, aristolone, solavetivone, and orientin obtained from Cyperus rotundus , have protective effects against lipid peroxidation, DNA damage, antihemolytic activity, and anticancer treatment for erythroleukaemia cells, which might be correlated with their high antioxidant activities [ 34 ]. Earlier experiments have also demonstrated that Alpinia galangal exerts in vitro antimelanogenesis activity [ 35 ] and in vivo antiamnesiac activity through its antioxidant properties [ 36 ]. In addition to their well-described in vitro antioxidant activities, several in vivo studies demonstrated that consumption of Allium sativum [ 37 ], Zingiber officinale [ 38 ], Terminalia arjuna [ 39 ], and Tinospora crispa [ 40 ] extracts led to significant increases in antioxidant enzymes, such as superoxide dismutase, glutathione peroxidase, and catalase, and suppressed glutathione depletion and lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant enzymes of SOD were increased to 7.17 ± 0.51 vs. 1.82 ± 0.44 U/min/mg in negative control. In addition, GPX (33.41 ± 1.48, vs. 21.84 ± 0.66 U/min/mg) and CAT (2.16 ± 0.18 vs. 0.90 ± 0.10 U/mg) were also elevated, along with non-enzymatic antioxidant vitamin C (0.92 ± 0.03 vs. 0.55 ± 0.03 μg/mg after treatment with A. galanga ( Table 3 ) [ 184 ]). Extracts of A. galanga could also inhibit MAO A and B activity at a low dose with a stronger inhibitory effect at a higher dose.…”
Section: Dysregulation Of Antioxidant and Pro-oxidant Enzymesmentioning
confidence: 99%
“…MAO is an enzyme that catalyzes the oxidative deamination of neurotransmitters including norepinephrine, serotonin, and dopamine, which have been suggested to increase H 2 O 2 generation in the neurons. Collectively, the attenuation of free radicals by the enhanced endogenous antioxidant system and the inhibition of MAO enzymes by A. galanga improved cognition in AD mice [ 184 ].…”
Section: Dysregulation Of Antioxidant and Pro-oxidant Enzymesmentioning
confidence: 99%